The Value of Normal Body Weight in Iceland - Brynja Jónbjarnardóttir 1994- (2018)
In this paper the monetary compensation needed to offset the welfare loss associated with being underweight, overweight or obese is measured. For this purpose, the compensated income variation (CIV) method is applied to panel data from an Icelandic health-and-lifestyle survey carried out in 2007, 2009 and 2012. Special attention is given to the problem of obesity, due to its health consequences and rapid growth in Iceland and other OECD countries. In that regard, it is examined whether the existing negative relationship between happiness and obesity is partly due to social stigma. Three model specifications are estimated, (i) one with basic control variables, (ii) another where obesity-related disease variables are included to eliminate the possible health mechanism and isolate the remaining effect, that could reasonably be considered a social-stigma effect, and (iii) where relationship status variables are excluded. The CIV estimates are almost identical for the first two models, indicating that social stigma due to obesity has considerable effect on happiness. The CIV estimates from model (i), (ii) and (iii) for obese females are $38,666 per year, $36,468 per year and $31,548 per year, respectively. The aggregated estimate of CIV for obese females in Iceland is then just over $1bn, or 4% of GDP.